Olive Fruit Fly Symbiont Population: Impact of Metamorphosis - Campos, Catarina; Gomes, Luis; Rei, Fernando T.; Nobre, Tania (Frontiers in Microbiology, 2022)
The current symbiotic view of the organisms also calls for new approaches in the way we perceive and manage our pest species. The olive fruit fly, the most important olive tree pest, is dependent on an obligate bacterial symbiont to its larvae development in the immature fruit. This symbiont, Ca. Erwinia dacicola, is prevalent trough host life stages, and we have shown significant changes in its numbers due to olive fruit fly metamorphosis. The olive fruit fly microbiota was analyzed through 16S metabarcoding, at three development stages: last instar larvae, pupae and adult. Besides Ca. E. dacicola, the olive fruit flies harbor a diverse bacterial flora of which 13 OTUs (grouped in 8 genera/species) were now determined to persist excluding at metamorphosis (Corynebacterium sp., Delftia sp., Enhydrobacter sp., Kocuria sp., Micrococcus sp., Propionibacterium sp., Pseudomonas sp., Raoultella sp. and Staphylococcus sp.). These findings open a new window of opportunities in symbiosis-based pest management.